Sangam Literature Learning, Teaching and Evaluation - (:unkn) unknown (My University, 2014)
This book of 10 articles and the explanatory details of literary terms makes an attempt to segregate various aspects of the Sangam poems and help the users to understand them from various angles.
Keywords: Tamil